2021
DOI: 10.1097/bot.0000000000001966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of a 6 am–9 am Dedicated Orthopaedic Trauma Room on Hip Fracture Outcomes in a Community Level II Trauma Center

Abstract: Objective: To assess the outcomes of elderly hip fracture surgeries performed 12 months before and 12 months after the implementation of a daily 6 AM-9 AM dedicated orthopaedic trauma room (DOTR) at a Level II community trauma center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
2
11
0
Order By: Relevance
“…This suggestion is consistent with the findings of several other improvement program studies, 35,77,105 where a consistently designated trauma room achieved lower TTS. Bellas et al 93 supported the potential of preoperative specialty consultations on hospitalist comanagement as an improvement program but suggested that consultations should be strategically used on a needs-only basis, rather than as standard practice.…”
Section: Jama Network Open | Health Policysupporting
confidence: 91%
See 3 more Smart Citations
“…This suggestion is consistent with the findings of several other improvement program studies, 35,77,105 where a consistently designated trauma room achieved lower TTS. Bellas et al 93 supported the potential of preoperative specialty consultations on hospitalist comanagement as an improvement program but suggested that consultations should be strategically used on a needs-only basis, rather than as standard practice.…”
Section: Jama Network Open | Health Policysupporting
confidence: 91%
“…190 studies underwent full-text review, and 69 studies were selected for final analysis (Figure and eAppendix 3 in the Supplement). Among the final 69 improvement programs, 49 programs significantly decreased TTS and 20 programs did not. Delayed TTS cutoffs were most often defined dichotomously as more than 24 hours, more than 36 hours, more than 48 hours, or more than 72 hours, although some studies collected continuous data.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…3 Other advantages with trauma room implementation include improvements in morbidity and complication rates, decreased intensive care unit (ICU) admissions, fewer unplanned surgeries, improved noncomplicated fracture union, enhancements in the professional and personal lifestyles of the oncall surgeon, and increased surgeon recruitment and retention. [3][4][5][6] Decreasing the time to operating room (TTOR) for hip fractures has been of particular interest to orthopaedic surgeons. [7][8][9] Improved morbidity and mortality outcomes have been associated with earlier hip fracture surgery.…”
Section: Introductionmentioning
confidence: 99%